COVID-19, Lockdowns and Well-Being: Evidence from Google Trends - Abel Brodeur; Andrew E. Clark; Sarah Fleche; Nattavudh Powdthavee (Global Labor Organization (GLO), 2020)
The COVID-19 pandemic has led many governments to implement lockdowns. While lockdowns may help to contain the spread of the virus, they may result in substantial damage to population well-being. We use Google Trends data to test whether the lockdowns implemented in Europe and America led to changes in well-being related topic search terms. Using differences-in-differences and a regression discontinuity design to evaluate the causal effects of lockdown, we find a substantial increase in the search intensity for boredom in Europe and the US. We also found a significant increase in searches for loneliness, worry and sadness, while searches for stress, suicide and divorce on the contrary fell. Our results suggest that people's mental health may have been severely affected by the lockdown.
Keywords: I12; I31; J22; 330; Boredom; COVID-19; Loneliness; Well-being